USE OF BIBLIOTHERAPY AS AN EFFORT TO PREVENT NEGATIVE STUDENT BEHAVIOR - Malini Lubis, Fatimah; Nur Ainun, Wa Ode; Munizu, Musran; Fathurohman, Apit (Jurnal Konseling Pendidikan Islam, 2023)
The purpose of this study was to find out the use of bibliotherapy to prevent negative behavior of students at school. The research method used by researchers was qualitative with a descriptive study approach, which was the focus of this research using the counseling technique of bibliotherapy to prevent negative behavior of junior high school students. Data collection techniques carried out included interviews, observation, and documentation studies of several documents related to the research topic. The results of this study indicate that the users of the bibliotherapy technique themselves are guidance and counseling teachers who are professionals, meaning they must be graduates or bachelors in guidance and counseling. While the use of bibliotherapy techniques has proven effective in preventing or reducing students' negative behaviors such as smoking, bullying, being disrespectful to teachers, and fighting, besides that kind of guidance and counseling, teachers use group guidance with discussion techniques. While for bibliotherapy, it is used during individual counseling.